Molecular Characterization of the Onset and Progression of Colitis in Inoculated Interleukin-10 Gene-Deficient Mice: A Role for PPARα. (20th May 2010) - Knoch, Bianca; Barnett, Matthew P. G.; Cooney, Janine; McNabb, Warren C.; Barraclough, Diane; Laing, William; Zhu, Shuotun; Park, Zaneta A.; MacLean, Paul; Knowles, Scott O.; Roy, Nicole C.
Abstract : The interleukin-10 gene-deficient (Il 10 - / - ) mouse is a model of human inflammatory bowel disease and Ppara has been identified as one of the key genes involved in regulation of colitis in the bacterially inoculatedIl 10 - / - model. The aims were to (1) characterize colitis onset and progression using a histopathological, transcriptomic, and proteomic approach and (2) investigate links between PPARα and IL10 using gene network analysis. Bacterial inoculation resulted in severe colitis inIl 10 - / - mice from 10 to 12 weeks of age. Innate and adaptive immune responses showed differences in gene expression relating to colitis severity. Actin cytoskeleton dynamics, innate immunity, and apoptosis-linked gene and protein expression data suggested a delayed remodeling process in 12-week-oldIl 10 - / - mice. Gene expression changes in 12-week-oldIl 10 - / - mice were related to PPARα signaling likely to control colitis, but how PPARα activation might regulate intestinal IL10 production remains to be determined.